Observing the character of public accountant through the spirit of Fastabiqul Khairat: Meneropong Karakter Akuntan Publik melalui Semangat Fastabiqul Khairat - Aripratiwi, Ratna Anggraini; Jannah, Binti Shofiatul; Lating, Ade irma Suryani; Hanun, Nur Ravita (Journal of Accounting Science, 2023)
This study aims to examine the character of public accountant in spirit fastabiqul khairat through a religius approach. The method used in this research is qualitative with a religiosity pradigm strategy. This study found that the spirit of fastabiqul khairat appears in every audit process, carried out by public accountant, starting from the engagement process to the issuance of an audit opinion. In the ethical crisis faced by public accountant, it takes a character building with integrity “amal shalih“ and not unjust. Public accountant prioritize aspects of conviction in every decision, adhere to the applicable rules. Through the spirit of fastabiqul khairat, it’s expected to be able to produce ethical behaviour for public accountant, which will lead to the concept of a code of ethics of public accountant profession.